Integration Interaction of the States Parties of the Eurasian Economic Union as a Factor in Ensuring their National Economic Security - L. N. Krasavina; N. V. Lukyanovich (Мир новой экономики, 2018)
The article discusses the main issues of integration interaction of EEU member states in the context of provision of their national economic security. It is noted the general and the particular in the concepts and national security policies of these countries, also different conceptual approaches to the development of indicators of national economic security are marked. The basic contradictions in the integration processes of the Eurasian space are analyzed and there are given some suggestions to minimize them. It was indicated to the need of research work intensification on the problems of Eurasian integration taking into account the growth of global instability.